272 TIME TO REFERRAL AND DIAGNOSIS OF CONGENITAL HEART DISEASE IN INFANTS. (1st January 2005) - Benjamin, J.; Romp, R.; Schelonka, R. L.
Abstract : Introduction: Severe congenital cardiovascular malformation (CCVM) occurs in 1 to 2 per 1000 live births. The outlook for newborns with CCVM has improved considerably, but these malformations still contribute morbidity and mortality in this age group particularly with delays in recognition and treatment. Aim: To determine the prevalence of late referral for infants with serious congenital cardiac anomalies. Methods: All neonates with CCVM admitted to Alabama's regional cardiovascular referral center from January 1, 1989 to June 30, 2004 were eligible for study. Demographic data and time of referral for cardiovascular evaluation were collected prospectively and maintained in a database. Medical records of a subset of these infants, admitted from January 1 to August 20, 2004, were reviewed retrospectively. Information on type of cardiac lesion, time of diagnosis, and various demographic variables was obtained. Infants with patent ductus arteriosus or ventricular septal defect as the only cardiac diagnosis were not included. Referral was considered late if it occurred after 2 days of age. Results: During the 15-year study period, 2390 infants were admitted with CCVM. 726 (30%) were referred for care after 2 days of age. During the study year, 2004, 59 infants were referred with CCVM. Overall, 19 infants (32%) were diagnosed after postnatal day 2. The figure shows the proportion of early and late referrals in study year 2004 for each cardiac diagnosis. Conclusion: More than 30% of infants with serious CCVM were referred for diagnosis and treatment after the second postnatal day. The high proportion of infants in whom diagnosis of CCVM is delayed underscores the need for earlier detection and referral.